2016
DOI: 10.1016/j.foodchem.2016.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of an oak chips-grape mix maceration process. Influence of chip dose and maceration time

Abstract: Oak chips-related phenolics are able to modify the composition of red wine and modulate the colour stability. In this study, the effect of two maceration techniques, traditional and oak chips-grape mix process, on the phenolic composition and colour of Syrah red wines from warm climate was studied. Two doses of oak chips (3 and 6g/L) at two maceration times (5 and 10days) during fermentation was considered. Changes on phenolic composition (HPLC-DAD-MS), copigmentation/polymerisation (spectrophotometry), and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
15
1
2
Order By: Relevance
“…Increasing the maceration time is useful to increase the concentration of anthocyanins, phenolic compounds, and consequently, the antioxidant activity of wine improves (Gomez‐Mıguez, Gonzalez‐Miret, & Heredia, ; Ivanova‐Petropulos, Durakova, Ricci, Parpinello, & Versari, ; Kelebek et al, ; Lingua, Fabani, Wunderlin, & Baroni, ). Besides, maceration is applied in wines that will be submitted to oak‐aging to improve the color stability (Gordillo et al, ; Heredia, Escudero‐Gilete, Hernanz, Gordillo, & Meléndez‐Martínez, ). Nonetheless, it is necessary to consider the phenolic compounds extractability, that may promote a high level astringency (Rinaldi, Iturmendi, Jourdes, Teissedre, & Moio, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the maceration time is useful to increase the concentration of anthocyanins, phenolic compounds, and consequently, the antioxidant activity of wine improves (Gomez‐Mıguez, Gonzalez‐Miret, & Heredia, ; Ivanova‐Petropulos, Durakova, Ricci, Parpinello, & Versari, ; Kelebek et al, ; Lingua, Fabani, Wunderlin, & Baroni, ). Besides, maceration is applied in wines that will be submitted to oak‐aging to improve the color stability (Gordillo et al, ; Heredia, Escudero‐Gilete, Hernanz, Gordillo, & Meléndez‐Martínez, ). Nonetheless, it is necessary to consider the phenolic compounds extractability, that may promote a high level astringency (Rinaldi, Iturmendi, Jourdes, Teissedre, & Moio, ).…”
Section: Introductionmentioning
confidence: 99%
“…() found that Primitivo wines made with completely destemmed berries had higher anthocyanin concentration but lower concentrations of other phenolics and lower colour intensity at racking and after 12 months storage, compared to wines made with partial destemming. In a similar vein, the addition of oak chips (3 and 6 g L −1 ) to the fermentation must for shorter periods (5 days) resulted in higher phenolic concentrations and improved colour characteristics compared to Syrah wines produced without them (Gordillo et al ., ); in contrast, a longer maceration time (10 days) resulted in lower colour stability, probably due greater absorption of phenolic compounds.…”
Section: Palatementioning
confidence: 93%
“…This effect may be related to polymeric anthocyanins which were created during the early steps of winemaking by condensation reactions between the anthocyanins themselves and other compounds given up by the wood or initially present in the wine as flavan-3-ols. In addition, the added wood could adsorb the anthocyanin compounds on its surface causing a decrease in its concentration especially when the amount of added wood was higher and the maceration period was longer [21]. Table 1.…”
Section: Phenolic Compound Analysismentioning
confidence: 99%